"Utopian in the Right Sense": The Responsibility to Protect and the Logical Necessity of Reform. Issue 3 (8th September 2017) - Hehir, Aidan
Abstract : In this article I argue that the claims made about the efficacy of the Responsibility to Protect (RtoP) echo the pejorative conceptions of "utopianism" as advanced by E. H. Carr and Ken Booth in two ways: through the determination of RtoP supporters to claim "progress" in spite of countervailing empirical evidence; and through the exaggerated importance that supporters ascribe to institutionalization, which mistakenly conflates state support with a change in state behavior and interests. I argue that RtoP's impact on the behavior of states has been and will continue to be limited. Moreover, while RtoP has garnered widespread support among states, this is due to it having been rendered largely impotent through a process of norm cooptation. While both Carr and Booth criticized a particular form of utopianism, they both also defended the articulation of normative prescriptions that are not immediately feasible. To this end, I conclude by suggesting a potential reform of the existing international legal order that meets Carr's preference for normative thinking that is "utopian in the right sense."